(untitled) (International Journal of Physiotherapy, 2023)
Background: Risk-taking behaviors have emerged as a target for fall prevention. However, the risk-taking concepts are complex, and several approaches exist to identify risk-taking behaviors. In addition, studies of fall-related risk-taking behaviors have not yet been systematically evaluated. Methods: This scoping review was conducted in accordance with Joanna Briggs Institute’s methodology for scoping reviews. Six electronic databases were searched to identify studies published between 2000 and 2020. Studies were included in our review if they were conducted on community-dwelling older adults (≥ 65 years) and discussed fallrelated risk-taking behaviors. Data extraction and analyses were completed using a table developed a priori by the research team. Results: Self-reported behaviors using qualitative methodology were the most common approach to identifying risktaking behaviors in community-dwelling older adults. Generally, older adults are aware of their fall risk and tend to adopt behaviours to help mitigate it. However, older adults also described moments of deliberate risk-taking driven by the potential benefits of this behavior. Factors associated with risk-taking include an individual’s abilities, personal values, and physical and social environment. Conclusion: This review demonstrated that fall-related risk-taking behaviors are a highly individualized concept influenced by a number of factors. Therefore, future research should evaluate how risk appraisal, risk attitudes, and risk propensity predict fall-related risk-taking behaviors in community-dwelling older adults.